Promoting Humanitude Care in Family Caregivers of Older Adults with Dementia - wudhiwong, kasinee; LeSeure , Peeranuch (Journal of Nursing, Siam University, 2023)
In Thailand, family caregivers, including husband, wife, child, and grandchild, play a significant role in caring for older adults with dementia in the family at home as part of Thai culture. Also, caring for older adults in the family is also a way children should be grateful to their parents/grandparents. However, providing long-term care for old adults with dementia could lead to exhaustion, stress, or burn out. This article aims to present the concept of humanitude care, which emphasizes respect for the dignity of the human person. The article will present the key principles and steps of humanitude care. It will also provide an alternative approach for nurses who provide care in the community to enhance family caregivers, knowledge and skills in caring for older adults with dementia using the humanitude concept. Therefore, family caregivers could provide proper care for older adults with dementia with less burden.